Does stapes surgery improve tinnitus in patients with otosclerosis? - Ismi,Onur (2017)
Abstract Introduction: Otosclerosis (OS) is the primary disease of the human temporal bone characterized by conductive hearing loss and tinnitus. The exact pathogenesis of tinnitus in otosclerosis patients is not known and factors affecting the tinnitus outcome in otosclerosis patients are still controversial. Objectives: To find the effect of stapedotomy on tinnitus for otosclerosis patients. Methods: Fifty-six otosclerosis patients with preoperative tinnitus were enrolled to the study. Pure tone average Air-Bone Gap values, preoperative tinnitus pitch, Air-Bone Gap closure at tinnitus frequencies were evaluated for their effect on the postoperative outcome. Results: Low pitch tinnitus had more favorable outcome compared to high pitch tinnitus (p = 0.002). Postoperative average pure tone thresholds Air-Bone Gap values were not related to the postoperative tinnitus (p = 0.213). There was no statistically significant difference between postoperative Air-Bone Gap closure at tinnitus frequency and improvement of high pitch tinnitus (p = 0.427). There was a statistically significant difference between Air-Bone Gap improvement in tinnitus frequency and low pitch tinnitus recovery (p = 0.026). Conclusion: Low pitch tinnitus is more likely to be resolved after stapedotomy for patients with otosclerosis. High pitch tinnitus may not resolve even after closure of the Air-Bone Gap at tinnitus frequencies.